2015
DOI: 10.1007/s12011-015-0238-2
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Studies of Molybdenum-Induced Apoptosis in Kidney Cells of Caprine

Abstract: Molybdenum (Mo) is an essential microelement for the health of animals and human beings, and high dietary intake of Mo can lead to pathological conditions. However, the cytotoxic effects of high levels of Mo on the renal cells in ruminants have not been reported. Therefore, this in vivo study in goats was designed to investigate the impact of Mo on kidney-related apoptosis genes, and histopathological and ultrastructural changes in renal cells using real-time quantitative polymerase chain reaction (RT-qPCR), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…It was previously reported that Cd could trigger liver cell apoptosis through activation of Caspase-3A [10], and Cd can induce apoptosis of chicken splenic lymphocytes by increasing mRNA levels of Bak, Caspase-3, and Caspase-9 and by decreasing Bcl-2 [19]. Additionally, high levels of Mo can result in unregulated expression of Bax, CytC, and Caspase-3, whereas it downregulates Bcl-2 in goat kidney [12]. Mo administration has induced an increase in Bax expression and a decrease in Bcl-2 expression in chicken kidney cells [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that Cd could trigger liver cell apoptosis through activation of Caspase-3A [10], and Cd can induce apoptosis of chicken splenic lymphocytes by increasing mRNA levels of Bak, Caspase-3, and Caspase-9 and by decreasing Bcl-2 [19]. Additionally, high levels of Mo can result in unregulated expression of Bax, CytC, and Caspase-3, whereas it downregulates Bcl-2 in goat kidney [12]. Mo administration has induced an increase in Bax expression and a decrease in Bcl-2 expression in chicken kidney cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Mo nanoparticles have induced intracellular reactive oxygen species (ROS) generation, mitochondrial membrane potential (MMP) changes, cell cycle arrest, and DNA damage [30]. Additionally, high levels of Mo can cause renal tubule degeneration, glomerular atrophy, nuclei deformation, and fracture in goat kidney [12]. …”
Section: Introductionmentioning
confidence: 99%
“…A deficiency or excess of Mo can cause damage to the body. Several minerals like arsenic, cadmium, lead and mercury are well known to be harmful to the well-being of animals and humans while many other metals, like chromium, manganese, molybdenum or selenium, are necessary but could be harmful over certain levels [2]. Molybdenum ores and fuel containing Mo are widely used in human activities (such as coal combustion), increasing the circulation of Mo in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Entropi molar standar mempunyai satuan Joule per mol kelvin (J/molK). Nilai S 0 bersifat absolut, tidak seperti entalpi pembentukan (160)(161)(162)(163)(164)(165) . Dimana keadaan standar suatu unsur nilainya tidak sama dengan nol yang pasti S berada pada suhu ruanagn.Struktur kristal murni mempunyai nilai entropi 0 J/molK pada suhu 0 K, menurut hukum termodinamika ketiga (166)(167)(168)(169) .…”
Section: Grafik Konduktivitasunclassified